Das EU-Investitionsschutzrecht im Wandel Analyse der aktuellen Rechtsprechung des EuGH zu Intra-EU-Investitionsschutzabkommen - Leeb, Matthias (Young Academics: Rechtswissenschaft, 2023)
Analysing European investment protection law, Matthias Leeb focuses on the resulting legal protection deficits for investors and provides concrete recommendations for dealing with them. In particular, he examines recent decisions of the ECJ on intra-EU investment protection agreements - Achmea, Komstroy, PL-Holdings and European Food SA, among others - and takes a critical look at them and their effects. Furthermore, the author addresses the EU's intended reform of investment protection in relation to third countries, taking into account current developments in the context of the Energy Charter Treaty (ECT).